2020
DOI: 10.1177/2045125320937908
|View full text |Cite
|
Sign up to set email alerts
|

The physical health and side-effect monitoring of patients prescribed clozapine: data from a clinical audit conducted in UK mental health services

Abstract: Background: In addition to mandatory haematological monitoring, treatment guidelines recommend routine monitoring of adverse effects and physical health in patients prescribed clozapine. Methods: NHS trusts/healthcare organisations participated in a clinical audit in the context of a UK quality improvement programme addressing clozapine-prescribing practice. Results: Data relating to 6948 adult patients prescribed clozapine were submitted by 63 NHS trusts/healthcare organisations. Of 481 patients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…However, several potentially life-threatening side effects are not detected by patient-compiled rating scales. An audit conducted in UK mental health services found that patient-compiled rating scales may be underutilized [ 111 ].…”
Section: Side Effect Monitoring and Managementmentioning
confidence: 99%
“…However, several potentially life-threatening side effects are not detected by patient-compiled rating scales. An audit conducted in UK mental health services found that patient-compiled rating scales may be underutilized [ 111 ].…”
Section: Side Effect Monitoring and Managementmentioning
confidence: 99%
“…Among the literature most closely related to this cluster, Ronaldson et al ( 18 ), Curto et al ( 19 ), Bellissima et al ( 25 ), Knoph et al ( 26 ), and Ronaldson et al ( 27 ) have the highest citation frequency and can represent the research base in this field. The top five cited studies, Barnes et al ( 28 ), Chopra et al ( 29 ), Kanniah et al ( 30 ), Brazile et al ( 31 ), and Anıl Yağcıoğlu et al ( 32 ), can represent the research frontiers in this field ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Current monitoring protocols include slow titration, close cardiac monitoring, and reduction of polypharmacy ( 54 ). In the early risk period of clozapine-induced myocarditis, monitoring results using inflammatory markers, such as C-reactive protein, and cardiac damage indicators troponin and brain natriuretic peptide are inconsistent ( 28 ). Therefore, investigators should not focus on the need to discontinue clozapine, but rather to provide more effective recommendations for monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The tool was designed to capture information from the clinical records related to clinical performance against seven evidence-based practice standards, which had been derived from the NICE Clinical Guideline CG178, ‘ Psychosis and Schizophrenia in Adults: Prevention and Management ’ ( NICE, 2014 ) and ‘ The Maudsley Prescribing Guidelines in Psychiatry ’ (2018), 13th edition. Five of these practice standards referred to medication review and monitoring of physical health and adverse effects, and performance against these standards has been reported elsewhere ( Barnes et al, 2020a ). Another practice standard concerned the ‘off-label’ prescription of clozapine, and the remaining standard addressed the management of a change in tobacco smoking habit: ‘For patients started on clozapine as inpatients, there should be consideration of the implications for dosage of any change in smoking status on discharge’.…”
Section: Methodsmentioning
confidence: 99%
“…This article reports on the findings of two clinical audits, conducted in 2019 and 2021, as part of the POMH QI programme on the use of clozapine (a receptor antagonist: D2, 5-HT2, NE alpha-2) in UK mental health services (Prescribing Observatory for Mental Health, 2019Health, , 2021. The methodology of the 2019 audit has been reported previously (Barnes et al, 2020a). Analysis of the data collected in both the audits identified possible areas for improvement in relation to the antipsychotic medication regimens prescribed before starting clozapine, the management of clozapine treatment during a change in smoking status and the inclusion of clozapine in a community patient's Summary Care Record (SCR).…”
Section: Introductionmentioning
confidence: 99%